Effects of nitroprusside, 3-morpholino-sydnonimine, and spermine on calcium-sensitive potassium currents in gastric antral circular myocytes of guinea pig - Li Ying; Xu Wen-Xie; Li Zai-Liu (Acta Pharmacologica Sinica; Vol 21, No 6 (June 2000): Acta Pharmacologica Sinica, 2016)
"AIM: To determine the effect of nitric oxide (NO) on calcium-activated potassium currents in antral circular myocytes of the guinea pig stomach. METHODS: The whole-cell patch-clamp techniques were used, and the cells were isolated by collagenase. Sodium nitroprusside (SNP), spermine, and 3-morpholino-sydnonimine (SIN-1) were used as nitric oxide donors. RESULTS: Outward potassium currents were remarkably inhibited by tetraethylammonium (TEA) 1 mmol.L-1. Charybdotoxin 200 nmol.L-1, a specific inhibitor of KCa channel, also greatly inhibited IK(Ca). NO donors remarkably increased IK(Ca) in guinea pig gastric antral circular myocytes with perforated patch-clamp techniques but not conventional whole-cell patch-clamp techniques. Spermine 100 mumol.L-1 increased IK(Ca) by 14% +/- 10% (at 60 mV, P < 0.01), SIN-1 200 mumol.L-1 increased IK(Ca) by 19% +/- 14% (at 60 mV, P < 0.01), and SNP 100 mumol.L-1 increased IK(Ca) by 24% +/- 13% (at 60 mV, P < 0.01) respectively. SIN-1- and SNP-induced increase of IK(Ca) was blocked by methylene blue 1 mumol.L-1. CONCLUSION: NO increases calcium-activated potassium currents in gastric antral circular myocytes of guinea pig, and the effect of NO on IK(Ca) may be mediated by cyclic GMP."